Generation and trapping of a mesoderm biased state of human pluripotency - Dylan Stavish (Nature Portfolio, 2020)
Application of pluripotent cells in regenerative medicine requires an understanding of how they exit pluripotency. Here the authors demonstrate support for the idea that pluripotency exit involves pluripotent intermediates that exhibit lineage bias by identifying and trapping a mesoderm biased sub-state in culture.